Sewing Brand Messages on Social Media: A Content Analysis of Cotton Incorporated’s Instagram Content Stimuli - Madalynn Kainer; Holli Leggette; Gary Wingenbach; Thomas Chappell; Karissa Palmer (Journal of Applied Communications, 2024)
Cotton is the most significant natural fiber in the world and an important part of the global economy. Yet, the cotton industry faces several challenges in securing its place in the global fiber market share, reaching new consumers, and maintaining relationships with current consumers. Furthermore, the cotton industry has a unique opportunity to share evidence-based information with followers through its product marketing on social media. The study described herein used content analysis to explore Instagram content on the @discovercotton profile. Content included categories of promoted products (i.e. women, men, children, or home); comments, posts, and caption stimuli; and most frequently used word, hashtag, and retail partner stimuli. We analyzed 434 Instagram stimuli (244 single photos, 142 carousels, and 48 videos) from March 2, 2021, to March 2, 2023. Across all stimuli, there were 110,143 likes and 5,799 comments with total response (engagement: likes and comments) reaching 115,942. We found that women’s products were promoted most often followed by men, home, and children—only 8.48% of stimuli depicted cotton, a cotton plant, or the seal of cotton. We identified six major themes in caption stimuli on @discovercotton: qualities of cotton, style, sustainability, check the label, women, and cotton production. Cotton was the most frequently used word stimuli in captions, and cotton as a fabric was the most promoted theme.
Keywords: cotton; content analysis; social media; stimulus-organism-response; women